The Nature of Moral Intuition (an Analysis of the Meanings and Kinds of the Intuition and Moral Intuition in the Works of Philosophers) - Ali Mahjour; Mohsen Javadi; Abolghasem Fana'ee (اخلاق وحیانی, 2019)
This article explains the term "moral intuition" in philosophy. After explaining the literal meaning of intuition and the evolution of the word's meaning in English and Persian, four common meanings of intuition in philosophy are explained: 1. Platonic or mystical intuition; 2. intuition of the principles of knowledge; 3. Kantian intuition 4. Empirical intuition. Then, the thoughts of the 20th-century thinkers are examined. In this study, we have attempted to examine the views of some of the most important intuitive moral philosophers in their works, and in this way, it will be showed that what are the characteristics of the moral intuition in the twentieth century.  Listing these characteristics, it will become clear that moral intuition is neither Platonic or mystical, nor Kantian, nor empirical, but "moral intuition" is one of the types of "intuition of the principle of knowledge."